Assessment of Completeness of Handwritten Prescriptions in Eastern Libya - Bousoik, Emira; Alhusadi, Nesrin; Alzawi, Hana; Ramadhan, Rehab; Albarassi, Rawaa (Libyan International Medical University Journal, 2023)
Background Prescriptions, medicolegal documents issued by physicians to patients, must be written accurately and clearly, contain all the required information, and adhere to the guidelines for prescription writing. In eastern Libya, most prescriptions are handwritten. Incomplete prescriptions might lead to serious medication errors.Aim The aim of this article was to assess the completeness of handwritten prescriptions issued by physicians working in eastern Libya.Method A total of 1,080 handwritten prescriptions were collected from pharmacies in different parts of the city of Derna and its suburbs in eastern Libya. After the exclusion of three prescriptions that were defined as illegible by the researchers, the 1,077 remaining prescriptions were examined for completeness against a checklist designed according to the guidelines of the World Health Organization (WHO).Results Most of the prescriptions (84.12%) did not contain the name of the prescribing physician. The patient's name was not mentioned on 16.06% of the prescriptions. Patient-related information was missing in most of the prescriptions. Most of the physicians (91.27%) prescribed drugs using their trade names. Drug strength, route of drug administration, and duration of therapy were absent in 29.61, 87, and 56.17% of the prescriptions, respectively. Only 26% of the prescriptions contained the date.Conclusion Most of the prescriptions inspected in this study had some deficiencies and did not adhere to the WHO guidelines.
Keywords: handwritten prescriptions; legibility; medication errors; Libya